A large intrathoracic parathyroid adenoma. Issue 6 (December 1976) - Daggett, P; Johnston, I D; Lowe, D
Abstract : A case is described in which an unusually large parathyroid adenoma was visible on the plain chest radiograph taken during the investigation of hypercalcaemia. This was diagnosed preoperatively and a scheme is suggested whereby such a disgnosis can now readily be made. The differential diagnosis is discussed ant the literature is reviewed.